Silicon attenuates nutritional disorder of phosphorus in seedlings of Eucalyptus grandis × Eucalyptus urophylla - Reis, Eduarda Gonçalves [UNESP]; de Paula, Rinaldo Cesar [UNESP]; de Souza Júnior, Jonas Pereira; de Mello Prado, Renato [UNESP]; Soares, Mariana Bomfim [UNESP]; Canteral, Kleve Freddy Ferreira [UNESP] (My University, 2024)
Background: Nutritional disorders of phosphorus (P), due to deficiency or toxicity, reduce the development of Eucalyptus spp. seedlings. Phosphorus deficiency often results in stunted growth and reduced vigor, while phosphorus toxicity can lead to nutrient imbalances and decreased physiological function. These sensitivities highlight the need for precise management of P levels in cultivation practices. The use of the beneficial element silicon (Si) has shown promising results under nutritional stress; nevertheless, comprehensive studies on its effects on Eucalyptus spp. seedlings are still emerging. To further elucidate the role of Si under varying P conditions, an experiment was conducted with clonal seedlings of a hybrid Eucalyptus spp. (Eucalyptus grandis × Eucalyptus urophylla, A207) in a soilless cultivation system. Seedlings were propagated using the minicutting method in vermiculite-filled tubes, followed by treatment with a nutrient solution at three P concentrations: a deficient dose (0.1 mM), an adequate dose (1.0 mM) and an excessive dose (10 mM), with and without the addition of Si (2mM). This study assessed P and Si concentration, nutritional efficiency, oxidative metabolism, photosynthetic parameters, and dry matter production. Results: Si supply increased phenolic compounds production and reduced electrolyte leakage in seedlings provided with 0.1 mM of P. On the other hand, Si favored quantum efficiency of photosystem II as well as chlorophyll a content in seedlings supplemented with 10 mM of P. In general, Si attenuates P nutritional disorder by reducing the oxidative stress, favoring the non-enzymatic antioxidant system and photosynthetic parameters in seedlings of Eucalyptus grandis × Eucalyptus urophylla. Conclusion: The results of this study indicate that Eucalyptus grandis × Eucalyptus urophylla seedlings are sensitive to P deficiency and toxicity and Si has shown a beneficial effect, attenuating P nutritional disorder by reducing the oxidative stress, favoring the non-enzymatic antioxidant system and photosynthetic parameters.
Keywords: Beneficial element; Macronutrient; Nutritional deficiency; Nutritional toxicity